Crisis and opportunity in the professions - Pava, Moses L.; Primeaux, Patrick (Research in ethical issues in organizations, 2005)
In both the for-profit and the not-for-profit sectors, there is increasing focus on bottom-line results. As organizational goals become ever more quantified, the role of the professional has changed. In almost every profession, a growing conflict of interest now exists between the push of the organization's highly specific and measurable goals on the one hand, and the pull of professional standards and values on the other hand. The purpose of this book is to identify, describe, and understand these conflicts of interests in a wide variety of professional fields. This volume includes articles on medicine, law, accounting, social work, clergy, insurance, computer professionals, and advertising experts, among others, written by experts in the fields. In addition, this volume includes a number of broader pieces related to the topic of professionalism. This volume documents evidence to support the contention that there is a growing crisis in the professions, one that is not limited to one or two professions. The good news is that there is ample evidence that, in every profession, there are opportunities for growth, as well. The professions are facing a defining moment. This volume explores how they might respond.